PENGGUNAAN MEDIA BUKLET PADA PEMBELAJARAN PENGELOLAAN SUMBERDAYA AIR BERBASIS KEARIFAN LOKAL PADA KALANGAN REMAJA KELURAHAN KANDRI KECAMATAN GUNUNGPATI KOTA SEMARANG - Khotimah, Chusnul; Indrayati, Ariyani (Edu Geography, 2016)
This study aims is to determine: The feasibility of booklet media of water resource management based on local wisdom, and determine the application of the environmental education using a booklet on water resource management based on local wisdom among teenagers in the Kandri village, and to know the results of the education. This research designed in a Pre-experiments carried out in the Kandri village with a total of 40 teenagers subjects. Data were analyzed using average difference of two different test average (t-test). Results showed that booklet media of water resource management based on local wisdomÂ  find out the feasibility by expert, teenagers very enthusiastic use booklet and it can improve teenagersâ cognitive outcomes. It can be seen from the comparison of teenagerâs cognitive improvement results before and after, an average pre-testt is from 58.37 and 81.62 post test results. The conclusions is media of water resource management based on local wisdomÂ  find out the feasibility by expert, greatly assist teenagers in the Water Resource Management Is Based On Local Wisdom education. Moreover, it can improve teenagersâ cognitive outcomes.